From comfortable to conflicted: a three-year longitudinal symptom evolution of problematic Internet use among junior high school students - Kang, Yanjun; Feng, Xun; Zhang, Tong; Yin, Kexin; Wang, Peng (Frontiers in Psychiatry, 2025)
BackgroundProblematic Internet use (PIU) is frequently regarded as a potential mental health concern and poses significant risks to the well-being of adolescents. Previous studies have predominantly focused on the influencing factors and harms of PIU, with less attention directed towards symptom manifestations and age differences, especially among junior high school students entering adolescence.MethodsThis study used network analysis to explore the core symptoms and symptom relationships of PIU among junior high school students over three years. This study recruited 302 sixth-graders (T1: M=11.6, SD=0.65) who were assessed using the Problematic Internet Use Scale four times, resulting in four networks.ResultsThe network analysis showed that at T1, ‘hard to control’ and ‘being conflicted’ had the highest correlation. At T2-T4,’being comfortable’ and ‘Feel bad mood’ exhibited the highest correlation. At T1 and T2, ‘being comfortable’ was the core PIU symptom, reflecting students’ psychological dependence on the Internet in early middle school. However, ‘being conflicted’ becomes the most critical symptom in later middle school as they age, revealing the increasing contradiction between cognition and behaviour. In general, “being comfortable”, “feel bad mood”, and “being conflicted”, which constitute the key nodes in the PIU relationship network, generally maintained high-intensity centrality across the four measurements. Network comparison tests indicated similar network structures and connection strengths across the four measurements, with no significant gender differences.ConclusionsThe current study indicated that in the early stage of junior high school, implementing precise interventions for the symptom of “being comfortable” may help prevent the further deepening of problematic Internet use, while in the later stage of junior high school, close attention should be paid to the problem of “being conflicted” among adolescents. In addition, interventions for problematic Internet use issues do not need to take gender into account. This study provides evidence for understanding the dynamic changes in PIU among junior high school students and serve as a reference for formulating more appropriate and effective prevention and intervention measures.